Treatment of comminuted radial head fractures with personalized radial head prosthesis produced with 3-dimensional printing technology - Safali, Selim; Eravsar, Ebubekir; Özdemir, Ali; Çiftci, Sadettin; Ertaş, Erkan Sabri; Aydın, Bahattin Kerem; Acar, Mehmet Ali (Journal of shoulder and elbow surgery, 2023)
The radial head is the forearm's pivot point for supination-pronation. Although radial head resection can be performed in comminuted radial head fractures, radial head prosthesis has gained popularity in order to prevent possible complications such as progressive valgus instability in the elbow and secondary ulnocarpal impaction that may develop due to proximal displacement of the radius. As for radial head prostheses, standard prosthetic designs do not provide the same results in everyone, and the alignment of the radial head and radial neck angle cannot be fully achieved. We believe that the radial head must be reconstructed with a complete anatomical implant. We designed and applied personalized prostheses to our patients, and in this study, we wished to share the 2-year results of these patients. In this study, 23 patients who had comminuted radial head fractures had personalized radial head prostheses inserted. Preoperative variables such as type of injury, age, side, additional ligament injury, operation time, number of radial head parts, neck angle of individual prosthesis, stem length, and stem diameter were noted. The mean operating time was 26 ± 9 minutes. One month postoperatively, after physical therapy, elbow range of motion, loss of strength compared to the opposite joint, Mayo elbow scores, QuickDASH scores, and patient satisfaction were evaluated. Patients were evaluated 2 years postoperatively. QuickDASH and Mayo elbow scores were satisfactorily good (mean QuickDASH score: 9.091, mean Mayo score: 91.08). According to the results of the patient satisfaction questionnaire, 16 of the 23 patients reported excellent satisfaction, 5 patients good satisfaction, and 2 patients moderate satisfaction. None of the patients reported poor results. Since personalized radial head prosthesis consists of a single monoblock, its surgical application consists of a single step and has a short operating time. As the applications in the literature increase and more studies are conducted, this subject will be better understood. Our study demonstrated that these patients, whose anatomies were individually replicated, achieved good range of motion and patient satisfaction. In fact, none of the patients reported negative results. In comminuted radial head fractures, surgical implantation of personalized radial head prosthesis is a treatment modality with easy application, short operating time, and good functional results.